Enrarecidos: Rubén Darío, Oscar Wilde and Cultural Space - Barros Grela, Eduardo (Huarte de San Juan. Filología y Didáctica de la Lengua, 2013)
In this study we review the aesthetic proposals of two relevant literary figures in the development of Modernism: Rubén Darío and Oscar Wilde. Both writers show evidence of feeling fascinated by the «strangeness » that had proved instrumental in previous literary movements, and seek to produce a space that is proper to their eccentric partners. Michel Foucault’s History of Madness and Edward Soja’s Thirdspace are the basis of this essay to look at the need to produce a space for those «strange» individuals, as they generate a certain cultural spatiality defined by a relation of power between the different dominant discourses and the transgressive aesthetics they represent. Rooting from a clear comparative ambition, this essay critically reads «Max Nordau» to assess the spatial conflicts that, according to Michel Foucault, are the main feature of the turn of the century from an epistemological perspective.